MATEMATIKA Sains dan Teknologi untuk kemanusiaan /Paul Suparno ; editor, Hongki Julie, Henry Pribawanto Suryawan - Hongki Julie; Herry Pribawanto Suryawan; Paul Suparno (Sanata Dharma University Press, 2016)
vi,133 hlm. : ilus. ; 25 cm.